Dynamic Modulation of Phasic and Asynchronous Glutamate Release in Hippocampal Synapses - Chang, Chun Yun (American Physiological Society, 2010)
Although frequency-dependent short-term presynaptic plasticity has been of long-standing interest, most studies have emphasized modulation of the synchronous, phasic component of transmitter release, most evident with a single or a few presynaptic stimuli. Asynchronous transmitter release, vesicle fusion not closely time locked to presynaptic action potentials, can also be prominent under certain conditions, including repetitive stimulation. Asynchrony has often been attributed to residual Ca(2+) buildup in the presynaptic terminal. We verified that a number of manipulations of Ca(2+) handling and influx selectively alter asynchronous release relative to phasic transmitter release during action potential trains in cultured excitatory autaptic hippocampal neurons. To determine whether other manipulations of vesicle release probability also selectively modulate asynchrony, we probed the actions of one thoroughly studied modulator class whose actions on phasic versus asynchronous release have not been investigated. We examined the effects of the phorbol ester PDBu, which has protein kinase C (PKC) dependent and independent actions on presynaptic transmitter release. PDBu increased phasic and asynchronous release in parallel. However, while PKC inhibition had relatively minor inhibitory effects on PDBu potentiation of phasic and total release during action potential trains, PKC inhibition strongly reduced phorbol-potentiated asynchrony, through actions most evident late during stimulus trains. These results lend new insight into PKC-dependent and -independent effects on transmitter release and suggest the possibility of differential control of synchronous versus asynchronous vesicle release.